EKONOMI RUMAH TANGGA DI ERA PANDEMI COVID - 19 DAN KEBIJAKAN PEMERINTAH - ARISMAN PARHUSIP (LP2MTBM MAKARIOZ, 2022)
The economic condition of the Indonesian people is currently unstable, therefore the government continues to strive torestore the Indonesian economy. The pandemic comes with all its negatives, as we now know that the impact of thispandemic greatly affects all aspects, especially the health and economic conditions of the community. The Covid-19pandemic that occurred in early 2020 has resulted in an economic downturn in Indonesia and the Government also appealsto the public to implement health protocols. The after effect is that many businesses go bankrupt and layoffs occur so thatmore and more household economies are experiencing difficulties in life. In order to tackle the COVID-19 outbreak with all itsimpacts, the Government of Indonesia has implemented various policies to protect the public and also stop the furtherspread of this outbreak. Some of these policies are implementing restrictions known as PPKM (Enforcement of Restrictionson Community Activities) for the entire territory of the Republic of Indonesia. This action has a good aim, namely protectingthe community from the COVID-19 outbreak and restoring life to the national economy. The government continues to striveto help restore economic conditions that are currently experiencing a slump, in particular increasing the household economyto the maximum with existing resources until the new normal era.